A Study on Student Satisfaction with the Management and Administration of Dormitories at Souphanouvong University - Inthavong, Vienganousouk; ANOLAC, Vira; SOULIYA, Toulakone; CHANHTHAHONG, Khamxay (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This study aimed to examine students’ satisfaction with the management and administration of the dormitories at Souphanouvong University. The study employed a quantitative research design. The target population consisted of students residing in the university dormitories from Years 1 to 4 during the 2024 –2025 academic year, totaling 134 students, of whom 107 were female. The primary instrument used for data collection was a questionnaire. The collected data were analyzed using descriptive statistics, including the mean and standard deviation (SD). The results of the study revealed that students’ satisfaction with dormitory management and administration ranged from low to moderate. Specifically, satisfaction with services and facilities, management and administration, welfare, and policies was generally at a low level overall. Meanwhile, satisfaction with rules and regulations, dormitory staff, and internal dormitory activities was found to be at a moderate level only.